Digital Marketing Solutions to Enhance Brand Awareness of Seyoul Cosmetics in VietNam - Le, Thi Huong Giang (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Business Administration; 2021-2025